Fieldwork in a context of decolonization: the example of a French overseas territory (New Caledonia) - Kowasch, Matthias (ERDKUNDE, 2014)
New Caledonia, a French overseas territory in the South Pacific that possesses more than 25% of the world’s nickel reserves, is currently undergoing a process of decolonization, after a period of Civil War in the 1980s. Balanced between demands for independence of the indigenous Kanak population and political affiliation to France, there is a spatial as well as a socio-economic and cultural division of the population. I argue for socially responsible research strategies in a cross-cultural and politically charged context, and outline some of the factors that influenced my own ethnographic work. The researcher’s family background and education affect the structure of relationships and behaviours. Self-presentation and institutional affiliation play an important role in daily fieldwork. Information and data collection as well as publication of research results have to respect intellectual property rights, which are tangible and intangible. An outsider position in a foreign culture can lead to discomfort, which can be tackled by working closely with local researchers and institutions. Research can be useful in this situation, if the results are made available to local people, political actors, and business.